Distentio Animi : a relação alma e tempo em Agostinho - Bustamante, João Francisco Cortes (2022)
The study aims to present the relationship between soul and time in Augustine (354-430). In Confessiones, written between 397 and 400, time is presented in Book XI as distentio animi. This principle is the philosophical problem for the dissertation research. The challenge is to analyse the path before this philosophical problem in works by the thinker of late ancient philosophy. Retrospective readings of previous works in the work Confessiones allow us to assess soul and time in order to establish how much semantic, theoretical and conceptual unity or difference occurs with the philosophical problem. The analysis proposes two quiditatives guiding questions: What is the soul? and What is time?. The first chapter is committed to answering about the soul. The challenge is to discuss the definitions of the soul and how the soul relates to the human being and the body, as well as the soul in the World. The second chapter addresses time. The aim is to delineate time without restricting it into a dichotomy towards eternity. For this, time is articulated within the framework of an order and how time is realised through a language. The third chapter details how the relationship between soul and time occurs, in which the philosophical problem of distentio animi is the arrival point. The exercise is to establish how time makes possible the ascension of the human being and the soul in the World in order to approach eternity.